Covalency Competition Induced Active Octahedral Sites in Spinel Cobaltites for Enhanced Pseudocapacitive Charge Storage. Issue 2 (4th December 2021) - Tang, Pei; Gao, Peng; Cui, Xuehao; Chen, Zhen; Fu, Qingfeng; Wang, Zixing; Mo, Ying; Liu, Hui; Xu, Chaohe; Liu, Jilei; Yan, Jiaxu; Passerini, Stefano
Abstract: Spinel cobaltites are widely presented as promising pseudocapacitive materials, however, a fundamental understanding of their structure–property relationship at an atomic level remains vague. Herein, their geometrical‐site‐dependent charge storage capability is investigated by substituting Co with inactive Zn and redox‐active Mn. Experimental and theoretical analyses reveal that redox‐active cations in octahedral sites contribute to enhanced capacitance, intrinsically determined by the covalency competition between tetrahedral and octahedral sites. The Zn 2+ incorporation leads to increased occupancy of Co in octahedral sites and 2.9× increased capacitance at 1 A g −1 current density, whereas the substituted Mn cations mainly sit in octahedral sites which can react with OH − upon cycling and separate on the spinel surface to reconstruct into δ‐MnO2 nanosheets, leading to 4× increased capacitance at 1 A g −1 current density with a detected K + ion intercalation. Thus, the exposure of redox‐active cations in octahedral sites and their intrinsic properties are influential in determining spinel oxides' pseudocapacitive properties. This work provides a general principle to optimize the pseudocapacitive properties of spinel cobaltites by deliberately selecting cations for substitution and controlling their distribution in octahedral/tetrahedral sites. It also offers a fundamental understanding of geometrical‐site‐dependent activity, and can effectively guide the development of spinel oxides for enhanced pseudocapacitance. Abstract : Covalency competition‐induced exposed octahedrally‐coordinated cations are considered as the active sites for boosting the pseudocapacitive performance of spinel cobaltite, and their intrinsic properties are influential in determining the reaction mechanism involved. This work offers a comprehensive understanding of the geometrical‐site‐dependent activity in spinel cobaltites, and the design concepts may extend to other applications.